Simplexity exttwosuperior or: How I Learned to Stop Worrying and Love Complexity in Development - and Prieto Martin, Pedr (2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex around how we practically capture and account for complexity across a variety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu and Aristotle, and with the help of a series of memorable diagrams, we attempt to alchemise development’s complexity into… a simple living tree. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psychology, philosophy, organisational development and software engineering– as a way to articulate essential complexity concepts. Insights emerging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presented by Prof. Chambers, Burns, Scoones and Ang in the previous seminars, to explore what complexity means in practice for development professionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Computer Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Packard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at the local level, the social mobilisation processes that resulted from the “indignados” movement in Spain and their use of ICT. At IDS, Pedro has investigated the drivers of adaptiveness in accountability interventions, as part of MAVC. He now coordinates the learning component of DFID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL supports DFID country offices to experiment with the use of emerging technologies to address development challenges.